New records of the genus Lecane Nitzsch, 1827 (Lecanidae: Ploima: Monogononta: Rotifera) from South of Vietnam - Dang, Phan Doan (Academia Journal of Biology, 2015)
Three species of the genus Lecane Nitzsch, 1827 newly recorded from Vietnam are Lecane elegans, L. grandis and L. paxiana, All the thee species were collected in Dong Nai river (Dong Nai province) and Co Chien river (Vinh Long province). Up to date, the total number of thirty five species recorded for Vietnam’s fauna, two of these species, viz. L. elagans and L. paxiana are rarely observed in nature. They occurred in Hoa An water-supply pump station (Dong Nai province) only and with low density of 4-6 individuals/species, meanwhile Lecane grandis is commonly appeared in the samples collected in Dong Nai and Co Chien rivers with high density. Apart from three species of the genus Lecane newly recorded for Rotifera fauna of Vietnam. Two species, Lecane furcata and L. tenuiseta, were recored in the Central of Vietnam, but were known for the first time in the South Vietnam.